Study of Pharmaceutical Compound Degradation in Liquid Waste Using Environmentally Friendly Nanotechnology-Based Photocatalysts - Nurul Arsy; Hafid Prasetyo; Hartiana Anas; Wa Siti Arabiya; Taip Gegetu (Casuarina: Jurnal Teknik Lingkungan, 2026)
Pharmaceutical compounds discharged into aquatic environments, such as antibiotics and analgesics, are resistant to natural degradation and pose risks including microbial resistance and ecological imbalance. This study investigates the application of nanotechnology-based photocatalysts, specifically TiO₂ nanostructures, for the degradation of pharmaceutical pollutants in wastewater. The photocatalyst was synthesized using a sol-gel method and characterized by XRD and SEM to confirm its crystalline structure and morphology. Degradation experiments were conducted on paracetamol and selected antibiotics under UV irradiation. Results indicated that TiO₂ nanostructured photocatalysts achieved up to 75% degradation within 120 minutes. The photocatalytic mechanism involves the generation of hydroxyl radicals that attack the chemical bonds of pharmaceutical compounds, producing simpler and less harmful byproducts. Enhanced degradation efficiency was observed with increased light intensity and larger surface area of the photocatalyst. Compared to conventional treatment methods, this approach is energy-efficient and does not generate hazardous residues. The findings highlight the potential of nanotechnology-based photocatalysis as a sustainable solution for pharmaceutical wastewater treatment, aligning with green technology initiatives in environmental engineering.